PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK UNTUK MENINGKATKAN SIKAP TOLERANSI PADA PEMBELAJARAN PENDIDIKAN PANCASILA SISWA KELAS II SEKOLAH DASAR - Rahma Fazriyah; Titin Sunaryati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop a Pop-Up Book learning medium to enhance students' tolerance in Pancasila Education for second-grade students at SDN Kedungwaringin 02. This development research employs the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The analysis phase involved curriculum needs analysis and student characteristics. The design phase focused on creating the Pop-Up Book medium. The development phase included the production and validation of the medium by experts in media, content, and language. The validation test results showed high feasibility percentages: 92% from media experts, 75% from content experts, and 97% from language experts. Thus, the medium was categorized as very feasible for use after revisions based on expert suggestions. In the implementation phase, the medium was trialed with second-grade students. The evaluation phase was conducted to measure the medium's effectiveness. The effectiveness test results showed an average score of 0.82, indicating that the Pop-Up Book medium is quite effective in improving students' cognitive learning outcomes and attitudes of tolerance.